The use of hyfrecation in the treatment of Verrucae, a case study. - Sullivan, Robert; O'Flynn, Deirdre (Podiatry Review)
An old but good definition of hyfrecation is; a form of high frequency eiectrosurgery where a low powered electrical impulses are delivered to the surface of the skin via a blunt or sharp electrode. (Sebben 1988). The application of the electrode has differing effect on the skin, either electrodessication, where the tissue is coagulated and desiccated without burning or electrofulguration where the skin is burnt causing carbonisation of the tissue. Current literature shows that hyfrecation itself does not interfere with nerve conduction due to its high frequency (Plant 2002, Gupta 2003, Fernando et al 2004), pain is caused by the heat generated in the tissue. When hyfrecation is used on Verrucae the area must be well anesthetised using a suitable local anaesthetic and appropriate infiltration. It is the author's experience that the lesion is best pared down prior to the use of the hyfrecator. Both techniques of electrodessication and electrofulguration are used to gain adequate access and depth in the removal of the Verrucae. Hyfrecation is contraindicated in patients with a pacemaker as there is the potential for interference for the frequency of the pulse generated (Bridenstine 1998).